Enhancing Conceptual Understanding of Heat and Thermodynamics through Innovation of Local Wisdom-Differentiated Physics Learning Media - Sartika, Dewi; Andi Rosman; Nur Intang (Universitas Muhammadiyah Makassar, 2025)
Physics learning in secondary schools often encounters challenges, including limited contextualization, low student motivation, and difficulties in grasping abstract concepts such as heat and thermodynamics. Addressing these issues, this research developed innovative physics learning media utilizing the Lumio by SMART application integrated with differentiated instruction and local wisdom. This study aimed to enhance the quality of physics learning and foster cultural awareness among students. Employing Educational Design Research (EDR) with the 4D (Define, Design, Development, and Dissemination) model, the research involved 33 senior high school students and one physics teacher from West Sulawesi. Validation by experts showed that the learning media achieved high validity (90.13%). Practicality tests with students and teachers indicated very practical outcomes, scoring 84.17% and 92.49%, respectively. The media's effectiveness was assessed through student learning outcomes, revealing that 87.87% of students met the Minimum Mastery Criterion, with an average N-Gain of 0.65, categorized as medium improvement. This research introduced a novel integration of differentiated pedagogy, modern digital technology, and local cultural elements, significantly improving conceptual understanding and accommodating diverse learning styles. The findings emphasize that culturally contextualized, differentiated instructional approaches enhance physics education, fostering inclusive and meaningful learning experiences. The developed media contributes positively to educational practice by aligning technological innovation with cultural preservation in physics learning.